Pengelolaan Supervisi Manajerial Pengawas di Dabin 7 UPTD Pendidikan Purwodadi - kustiyani, kustiyani (Jurnal VARIDIKA, 2016)
Implementation of managerial supervision is the activities carried profesioal superintendent of schools in order to assist the principal in order to improve the quality and effectiveness of the education and learning. This study aimed to describe the managerial supervision planning, implementation of managerial supervision, and feedback managerial supervision supervisor in Dabin 7 UPTD District of Purwodadi. Qualitative research and ethnography with research subjects school supervisors and principals. Data collection techniques with interviews, observation, and documentation. Data analysis techniques to the analysis of the flow of the process of collecting data through data reduction, data display and verification. The validity of the data using triangulation and source. The results of the study, 1) Planning managerial supervision include, a. Preparation of supervision schedule manajejerial, b. Preparation of Instrument managerial supervision, c. Compile a list of schools to be supervised. 2) Implementation of supervision manajerial.Ada three stages in the implementation of managerial supervision, namely, initial activity, performance or core activities and the closing 3) The function of feedback is to improve the managerial supervision findings of non-compliance or overcome the problems identified, so as to improve the quality and effectiveness of education.